Penerapan Metode Service Quality untuk Mengetahui Kualitas Pelayanan Kantor Desa Sambirejo Timur Berbasis Web - Syauqi, Ahmad; Rini Oktari Batubara (Universitas Methodist Indonesia, 2025)
Sambirejo Timur Village was established on June 15, 1999. Services at the Sambirejo Timur Village Office begin with the reception of visitors who come for various administrative purposes. The purpose of this research is to ensure that all village administrative activities are neatly recorded, as well as to facilitate monitoring and evaluation of service quality. This procedure is expected to create a transparent and accountable environment in every service to the people of Sambirejo Timur Village. The research problem that occurs is that there are many suggestions and criticisms from the community about the services provided at the Village Office, but the delivery is not given directly through the criticism and suggestion box but through expressions from the surrounding community. In this study, the application of the service quality method is used to determine the quality of service at the Sambirejo Timur Village Office. The results of this study will be the application of the service quality method to determine the quality of service at the Sambirejo Timur Village Office, which is made in the form of a web application. The contribution of this research is to use the application of the digitalization/web-based service quality method at one of the agencies, namely the Sambirejo Timur Village Office.